Critical elements for multigenerational teams: a systematic review. Issue 7 (14th October 2019) - Burton, Cherise M.; Mayhall, Chrissa; Cross, Jennifer; Patterson, Patrick
Abstract : Purpose: Therefore, the purpose of this paper is to review the existing literature on multigenerational teams, to evaluate the maturity of the research area, identify key themes, and highlight areas for future research. Generational differences in the workforce are becoming a critical factor, as four generations (Veterans/Traditionalists, Baby Boomers, Generation X and Generation Y/Millennials) currently co-exist, and a fifth generation (Generation Z) stands poised to enter the workforce. To manage these differences effectively, organizations must first understand the various generations and, ultimately, their interaction and engagement with each other. Whereas some literature on the differences between the generations and how they pertain to the organizational work environment exists, currently, it is unclear what is known about how these differences impact the performance of multigenerational teams. Design/methodology/approach: This paper presents a systematic literature review on teams and generational differences. A total of 7 platforms were included, resulting in 121 articles in the final paper set. Findings: The review confirmed a low presence of literature related to generational differences and teams, implying the knowledge area is currently immature; however, despite this, there is an upward trajectory in publications and citations over the past few years, and existing publications and citations span a number of countries, suggesting a likelihood of significant growth in the research area in the near future. Further, key themes were identified in the current literature relating to commitment, leadership, team dynamics, conflict and wages and work environment. Research limitations/implications: Only seven platforms were included in this review, although the seven platforms chosen are believed to provide comprehensive coverage of the field. The search strings used were "generation" and "team, " which was the word combination found to produce the largest number of results in preliminary trials; however, it is possible that using additional word combinations might have yielded some additional papers. Finally, the review was limited to English-language articles (or their translations); although, ultimately, only two articles were eliminated because of lack of an English language version. Practical implications: The findings can be used by organizations to identify factors of interest in managing multigenerational teams, as well as what is currently known about influencing those factors to achieve more positive team outcomes. Originality/value: To the best of the authors' knowledge, this appears to be the first systematic literature review on generational differences in teams. Given the importance of this topic, this review is critical to provide a baseline on what is currently known in the field and existing research and practice gaps.